Empowering Educators: The Role of Self-Directed Learning in Teacher Professional Development - Erin West (Adult Education Research Conference, 2025)
This study examines teacher-directed professional learning through adult learning theories, focusing on self-directed learning (SDL). By reviewing recent literature, it explores SDL's role in empowering educators' autonomy, professional growth, and adaptability in modern education.
Keywords: Self-Directed Learning (SDL); Teacher Professional Development; Adult Learning Theory; Teacher Autonomy